PEMBUATAN MESIN PENGGULUNG KOIL OTOMATIS PT. SELAMAT SEMPURNA, Tbk. - , DEVANDIA RIKO C.K ([Yogyakarta] : Universitas Gadjah Mada, 2014)
PT. Selamat Sempurna, Tbk. is a factory engaged in manufacturing automotive filters. One of the machines used to make the filter cover is a projection welding machines. Projection welding machine has a flange mounted. The flange mounted often damaged in the coil windings part. It is made by utility technicians manually, Therefore that activity spend more time and is limited stock in flange mounted. Avoiding the limited of stock flange mounted coil better use a roller automatic machine. There are some steps that followed in the preparation of this project. First all design the machine by using AutoCAD and SolidWork softtware. Second develop six parts of the machine contain of table machine, jigs, motor holder, coil holder, counter holder and proximity sensor holder. While third third make electrical circuit and assembling the automation system by conecting all the equipments that consist of: relays, power supply 24V, cables 0.75 mm, oriental motor gearbox, capacitor, push button, emergency stop button and proximity sensor. The result of this project is a coil roller automatic machine. The roller speed is 41 rpm equiped with a 40 mm jig diameter. The coil windings can be used as a magnet flange mounted. It can support the maintenance division's to replace the damage flange mounted effectively.